A Survey for Human Papilloma Virus Infection among Women Attending Gynaecology Clinic of Jos University Teaching Hospital Jos, Nigeria - Zakari, H; Seri B.F; Anejo-Okopi,J.A; Ajang, A,Y; Katnap, S.R; Adabara, U.N. (UMYU Journal of Microbiology Research)
Human papilloma virus (HPV) is among the well known causes of cervical cancer and it represents the third most common malignancy in women, however surveillance data on its incidence rates are still needed in this part of the world. Accordingly, this study was conducted to determine the incidence of human papilloma virus in sexually active women aged between 18 and 65 attending gynaecology clinic of Jos University Teaching Hospital, Nigeria (In 2016) using enzyme linked immunosorbent assay ElISA kits (Cusabio Biotech. USA). A total of 90 blood samples was collected and analyzed according to manufacturer’s instructions. Out of the samples 28(33.3%) were found to be positive for Human Papilloma virus infection. The incidence of Human Papilloma virus in relation to age shows that those in the age group 16-25 had the highest rate of occurrence of 45.8%, followed by age 36-45(27.8%). Age groups 26-35, 46-55 and 56-65 years have 25.0% respectively. HPV incidence rate of 33.3% was found among women that are not single while 31.0% occurred among the married women. Women with diabetes had 50% incidence of HPV infection while 29.3% occurred among women without diabetes, equally HPV incidence rate of 37.5% occurred among women who had protected sex while 30.5% occurred among women that had unprotected sex. In conclusion high incidence of HPV was detected among the study population, hence, it is recommended that HPV vaccination should be included in the routine immunization among the gynaecology services for sexually active women and regular pap smear screening should be made mandatory.